2019
DOI: 10.1016/j.ijrobp.2019.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy as a Bridging Strategy for CAR T Cell Therapy With Axicabtagene Ciloleucel in Diffuse Large B-Cell Lymphoma

Abstract: Purpose: Axicabtagene ciloleucel (axi-cel) is a CD19-directed chimeric antigen receptor (CAR) T-cell therapy for relapsed or refractory diffuse large B-cell lymphoma. Bridging therapy may be required for lymphoma control during the manufacturing interval between collection of autologous T cells and final CAR T product administration. The optimal bridging therapy is not known and patients are often chemorefractory. We present a case series of patients receiving radiation as a bridge to axi-cel. Methods and Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 26 publications
1
96
0
1
Order By: Relevance
“…In the RT field. 6 In the current study, median dose was 35 Gy, with a smaller median fraction size of 2.5 Gy, without an apparent impact of dose on PFS. For DLBCL patients treated with salvage RT, doses .40 Gy may improve local control.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In the RT field. 6 In the current study, median dose was 35 Gy, with a smaller median fraction size of 2.5 Gy, without an apparent impact of dose on PFS. For DLBCL patients treated with salvage RT, doses .40 Gy may improve local control.…”
Section: Discussionmentioning
confidence: 55%
“…Often oncologists address this dilemma with bridging therapy (BT; commonly referred to as therapy administered after apheresis and before CAR T-cell infusion), which may include steroids, chemotherapy, targeted therapy, or radiation therapy (RT). 5,6 However, the ZUMA-1 trial that led to axi-cel approval did not permit the administration of BT other than dexamethasone. 1 It is unclear if BT adversely affects outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been described in cell lines and solid tumors. Recently, the outcomes of 8 patients who were treated with radiation therapy while waiting for CAR T cell manufacturing showed that the approach is a safe and effective method of obtaining local disease control, suggesting that post-CAR T radiation similarly might be safe [68]. Data supporting the role of radiation therapy in hematologic malignancies before CAR T cell therapy are limited.…”
Section: Late Relapse (3 Months After Infusion)mentioning
confidence: 99%
“…In the current issue of the International Journal of Radiation Oncology, Biology, Physics, Sim et al retrospectively report their experience using radiation therapy to help bridge 12 patients who were planned for axi-cel as they awaited availability of their personalized CAR T-cell products. 7 Although ZUMA-1, the registrational trial for axi-cel, did not permit bridging therapy, the authors point out that bridging is commonly used with commercial standard of care axi-cel. 5,8 The majority of the patients in their series were in desperate condition, with 2 to 5 (median 2) prior lines of therapy, 8 out 12 with bulky (10 cm) disease, and 6 of 12 with double hit lymphomas.…”
mentioning
confidence: 99%